The Australian Educational Researcher A Publication of the Australian Association for Research in Education - Mockler, Nicole; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Australian Educational Researcher is the international, peer reviewed journal published by AARE. The Australian Educational Researcher is published three times a year and is a Thomson (ISI) indexed journal. The aim of AER is to: Promote understandings of educational issues through the publication of original research and scholarly essays. Inform education policy through the publication of papers utilising a range of research methodologies and addressing issues of theory and practice. Provide a research forum for education researchers to debate current problems and issues. Provide an international and national perspective on education research through the publication of book reviews, scholarly essays, original quantitative and qualitative research and papers that are methodologically or theoretically innovative. AER welcomes contributions from a variety of disciplinary perspectives on any level of education.
Keywords: Education; Educational policy; ducation and state; Teaching; Educational psychology; Education -- Psychology; Education, general; Teaching and Teacher Education; Educational Policy and Politics; Educational Psychology